The Impact of Growth, Labour Cost and Working Time on Employment: Lessons from the French Experience - Yannick L'Horty; Christophe Rault (Institute for the Study of Labor (IZA), 2003)
To account for employment evolutions at the macro-economic level, we propose a modelling where employment is explained by added value, working time and real labour cost. Estimations using quarterly French macro-economic data are carried out in a multivariate framework for three sets of sectors. We get a relationship in which employment rises with growth and decreases when labour cost or working time rises in industrial sectors as well as in non-industrial ones. This model then permits to measure retrospectively the contributions of each of the variables to employment inflections since the mid-eighties.
Keywords: J22; E24; J23; 330; Per capita productivity; hourly productivity; labour demand; employment; working time; cointegration; VAR-ECM model; Beschäftigung; Wirtschaftswachstum; Arbeitszeitflexibilisierung; Arbeitskosten; Industrie; Dienstleistungssektor; Schätzung; Arbeitsproduktivität; Arbeitsnachfrage; Beschäftigungseffekt; Frankreich